2021
DOI: 10.3390/cells10092271
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cellular and Animal Inflammatory Disease Models by NF-κB Inhibitor DHMEQ

Abstract: General inflammatory diseases include skin inflammation, rheumatoid arthritis, inflammatory bowel diseases, sepsis, arteriosclerosis, and asthma. Although these diseases have been extensively studied, most of them are still difficult to treat. Meanwhile, NF-κB is a transcription factor promoting the expression of many inflammatory mediators. NF-κB is likely to be involved in the mechanism of most inflammatory diseases. We discovered a specific NF-κB inhibitor, dehydroxymethylepoxyquinomicin (DHMEQ), about 20 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 79 publications
0
14
0
1
Order By: Relevance
“…Previous studies demonstrated that targeting the NF-κB signaling pathway could prevent the progression of inflammation and ameliorate bone erosion in arthritis mouse models [ 33 , 34 ]. Moreover, some clinical drugs, such as iguratimod, show sustained efficacy in RA by inactivating NF-κB [ 35–37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that targeting the NF-κB signaling pathway could prevent the progression of inflammation and ameliorate bone erosion in arthritis mouse models [ 33 , 34 ]. Moreover, some clinical drugs, such as iguratimod, show sustained efficacy in RA by inactivating NF-κB [ 35–37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, for many tumors the prognosis is difficult to obtain from the expression level of APOE alone. In addition, previous research indicated that diet could impact the levels of APOE expression [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that HIF-1 α can activate the NF- κ B pathway and increase the secretion of cytokines such as TNF- α and IL-6 in the early stages of a cytokine storm [ 25 , 26 ]. In addition, dehydroxymethylepoxyquinomicin (DHMEQ) can inhibit NF- κ B activation and reduce inflammatory cytokine expression [ 27 ]. As shown in Figure 2 , NF- κ B pathway can promote autoimmunity and inflammation when it is aberrantly activated in different cell types.…”
Section: Signaling Pathways Related To Ali/ardsmentioning
confidence: 99%